An analytical study of the relationship between empowerment and critical factors for total quality management from the point of view of managers at Al Baraka Bank Algeria - Elmessaoud, Rebie; Ouda, Radia (Finance and Business Economies Review, 2020)
This study is aimed to know the realization managers in Al Baraka Bank Algeria’s concept of empowerment and critical factors of total quality management and their application in the bank's branches. And highlight the relationship between empowerment and critical factors. study concluded that there is a high awareness of the independent variable and empowerment as well as the dependent variable factors critical to TQM. And that there is a strong relationship between empowerment and critical factors of total quality management, that means when empowerment is practiced correctly we get more critical factors of TQM